(untitled) (AmS-Skrifter, 2020)
There was a strong influence from the Low German language on the languages in Scandinavia in late medieval times due to the considerable economical and cultural contact and interaction between northern Germany and the Scandinavian countries in this period, especially the Hanse trade. The vocabulary was especially affected, but also the grammatical structure and names. Some place-names from south-western Norway seem to reflect Low German influence. The loans from Low German are well integrated and adjusted to the structure of the Scandinavian languages.